2009
DOI: 10.1007/s12663-009-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various approaches for exposure of infraorbital rim fractures of zygoma

Abstract: Objective The aim of this study was to randomly compare four incisionssubciliary, subtarsal, infraorbital and transconjunctival with lateral canthotomy for treatment of orbital rim or floor fractures. Methods 40 patients with zygomatic complex fractures either isolated or in association with pan facial fractures, were selected for the study. They were divided into four groups of 10 patients each, Group I-Transconjunctival with lateral canthotomy, Group II-Subciliary [single eyelid incision], Group IIISubtarsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
2
24
0
11
Order By: Relevance
“…The risk of developing postoperative eyelid retraction also varies with the type of approach used to expose the inferior orbital rim and floor. [10,15] Few authors [2,3,10,15] have compared subciliary approach with transconjunctival approach but no study has tried the comparison with 'sutureless' transconjunctival technique on the basis of so many pre-defined parameters with a follow-up of 3 months. We observed that main drawbacks of the subciliary approach include the post-operative scarring and the risk for potential complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The risk of developing postoperative eyelid retraction also varies with the type of approach used to expose the inferior orbital rim and floor. [10,15] Few authors [2,3,10,15] have compared subciliary approach with transconjunctival approach but no study has tried the comparison with 'sutureless' transconjunctival technique on the basis of so many pre-defined parameters with a follow-up of 3 months. We observed that main drawbacks of the subciliary approach include the post-operative scarring and the risk for potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although it may seem that the difference lies only at the level of the incision from the ciliary margin, the anatomy of the region and the plane of dissection also influence the final aesthetic result [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional approach to the infraorbital rim/orbital floor has been by cutaneous infraciliary incisions namely the subciliary, mid lower eyelid or subtarsal and infraorbital incisions. These approaches leave behind a scar which may be cosmetically disfiguring at times [2]. The Frost suture is a novel technique to oppose downward tension vectors and to preserve or restore to position of lower eyelid.…”
Section: Introductionmentioning
confidence: 99%